The Concept of Mental Toughness: Tests of Dimensionality, Nomological Network, and Traitness. Issue 1 (27th February 2014) - Gucciardi, Daniel F.; Hanton, Sheldon; Gordon, Sandy; Mallett, Clifford J.; Temby, Philip
Abstract Mental toughness has received increased scholarly attention in recent years, yet conceptual issues related to its (a) dimensionality, (b) nomological network, and (c) traitness remain unresolved. The series of studies reported in this article were designed to examine these three substantive issues across several achievement contexts, including sport, education, military, and the workplace. Five studies were conducted to examine these research aims—Study 1: N = 30; Study 2: calibration sample (n = 418), tertiary students (n = 500), athletes (n = 427), and employees (n = 550); Study 3: N = 497 employees; Study 4: N = 203 tertiary students; Study 5: N = 115 army candidates. Collectively, the results of these studies revealed that mental toughness may be best conceptualized as a unidimensional rather than a multidimensional concept; plays an important role in performance, goal progress, and thriving despite stress; and can vary and have enduring properties across situations and time. This series of studies provides a foundation for further basic and applied research of mental toughness across various achievement contexts.